1995
DOI: 10.1006/dbio.1995.1184
|View full text |Cite
|
Sign up to set email alerts
|

Five Trk Receptors in the Zebrafish

Abstract: Using a homology-based cloning strategy we have identified five members of the Trk family in the zebrafish Danio rerio. They are homologous to the three mammalian Trk receptors in their conserved intracellular kinase regions and the organization of their extracellular regions. The five trk genes are differentially expressed in the developing brain, spinal cord, cranial ganglia, and retina. Full-length forms of three of the trk genes are expressed when neurons pioneer the major axon tracts, whereas the two othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
91
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(95 citation statements)
references
References 0 publications
4
91
0
Order By: Relevance
“…1C,D). Additionally, neither subpopulation overlapped with the larger trkA (nerve growth factor receptor)-expressing population (17.38±1.66 cells/ganglion) (Knaut et al, 2005;Liu and Ma, 2011;Martin et al, 1995) (Fig. 1D, supplementary material Fig.…”
Section: Subtype-specific Gene Expression Of Trigeminal Sensory Neuronsmentioning
confidence: 98%
“…1C,D). Additionally, neither subpopulation overlapped with the larger trkA (nerve growth factor receptor)-expressing population (17.38±1.66 cells/ganglion) (Knaut et al, 2005;Liu and Ma, 2011;Martin et al, 1995) (Fig. 1D, supplementary material Fig.…”
Section: Subtype-specific Gene Expression Of Trigeminal Sensory Neuronsmentioning
confidence: 98%
“…Bony fish orthologs of NGF, BDNF, NT-3 and NT-4/5 as well as of TrkA, TrkB and TrkC are known [Hallböök et al, 1991;Götz et al, 1994;Martin et al, 1995;Dethleffsen et al, 2003]. A complete set of the 'core' four neurotrophins were retrieved in two pufferfish (Takifugu rubripes and Tetraodon nigroviridis) and the zebrafish (Danio rerio) genome assemblies.…”
Section: Neurotrophins In Bony and Cartilaginous Fishesmentioning
confidence: 99%
“…NT-6/7 as well as fish NGF bind and activate TrkA and their expression suggests that subfunctionalization and to some degree neofunctionalization have occurred after the duplication [Dethleffsen et al, 2003]. Two paralogs of TrkB and of TrkC receptor genes have been identified in both zebrafish [Martin et al, 1995] and pufferfish genomes (TrkB1, TrkB2, TrkC1 and TrkC2) [BenitoGutierrez et al, 2006]. Phylogenetic analysis unambiguously shows that fish NT-6/7 and NGF evolved from the same ancestor and that those two genes, the fish TrkB1 -TrkB2 and TrkC1 -TrkC2 paralogs emerged from 'bony fish-specific' duplications.…”
Section: Neurotrophins In Bony and Cartilaginous Fishesmentioning
confidence: 99%
“…With regard to teleost fish, BDNF expression has been confirmed in the brain of the southern platyfish [Götz et al, 1992], in the developing zebrafish brain and retina [Hashimoto and Heinrich, 1997;Lum et al, 2001], and in the tench retina [Caminos et al, 1999]. Five neurotrophin receptors have been described in zebrafish [Martin et al, 1995], two of which have been reported to be isoforms of the Trk B receptor and their mRNA is widely distributed throughout the brain and spinal cord of larval zebrafish [Martin et al, 1995]. Hannestad et al [2000] observed immunoreactivity for Trk B in the adenohypophysis, striatum and retina during development of Dicentrarchus .…”
Section: Introductionmentioning
confidence: 99%